Scorpion neurotoxin AaIT-expressing Beauveria bassiana enhances the virulence against Aedes albopictus mosquitoes - Sheng-Qun Deng; Qun-Di Cai; Ming-Zhi Deng; Qiang Huang; Hong-Juan Peng (AMB Express, 2017)
Abstract To improve the insecticidal efficacy of this entomopathogen Beauveria bassiana, the fungus was genetically modified to express an insect-specific scorpion neurotoxin AaIT. The virulence of the recombinant B. bassiana strain (Bb-AaIT) against Aedes albopictus adults (which occurs via penetration through the cuticle during spore germination or by conidia ingestion), and the larvae (by conidia ingestion) was measured with bioassays. The median lethal concentration (LC50) of Bb-AaIT against A. albopictus larvae was 313.3-fold lower on day 4 and 11.3-fold lower on day 10 than that of the wild type (WT). Through conidia feeding or body contact, Bb-AaIT killed 50% of adult female mosquitoes at 3.9- or 1.9-fold reduced concentrations on day 4 and at 2.1- or 2.4-fold reduced concentrations on day 10. Compared with the results for the WT, the median lethal time (LT50) of Bb-AaIT was reduced by 28.6% at 1 × 107 conidia ml−1 and 34.3% at 1 × 106 conidia ml−1 in the larvae bioassay by conidia ingestion, while it decreased 32.3% at 1 × 107 conidia ml−1 by conidia ingestion and 24.2% at 1 × 108 conidia ml−1 by penetrating through the cuticle in the adult bioassay. All the differences were significant. Our findings indicated that Bb-AaIT had higher virulence and faster action than the WT in killing the larval and adult mosquitoes, and therefore, it is valuable for development as a commercial mosquito pesticide.